Instructor perception of Spanish heritage speakers’ pronunciation and effect on classroom experience - Reinsch, Bethany Lynn (My University, 2026)
Classroom practices for Spanish heritage speakers have improved in recent years, but more research is still necessary to ensure the success of this large group of students. This study, grounded in Vygotsky’s (1987) sociocultural theory, Labov’s (1966), sociolinguistic theory, and Krashen’s (1982) Affective Filter Hypothesis, investigates the classroom experiences of Spanish heritage speakers and identifies areas in which language ideologies held by instructors may affect teaching, especially regarding pronunciation. The research focused on the extent to which instructors are aware of features of speech common in heritage speakers and how this affects their teaching, especially in terms of the type of oral feedback they provide to students and spoken explicit explanation (or lack thereof) of pronunciation. Students and instructors from universities in Kansas that offer Spanish heritage courses responded to a questionnaire about their experiences with Spanish and in Spanish classrooms. The students recorded two speech samples, and the instructors listened to them to determine whether they were recorded by Spanish heritage speakers or second language learners. The instructors were able to identify second language learners more accurately. Additionally, the majority of student responses reflected positive attitudes towards their classroom experiences, indicating that, although there is a broad range of heritage speakers and instructors cannot always accurately identify them, the effects on classroom practices are not particularly strong in Kansas universities.
Keywords: Heritage speakers; Pronunciation; Feedback; Classroom experience